Advisor Value-Added and Student Outcomes: Evidence from Randomly Assigned College Advisors - Serena Canaan; Antoine Deeb; Pierre Mouganie (Institute of Labor Economics (IZA), 2019)
This paper provides the first causal evidence on the impact of college advisor quality on student outcomes. To do so, we exploit a unique setting where students are randomly assigned to faculty advisors during their first year of college. We find that higher advisor value-added (VA) substantially improves freshman year GPA, time to complete freshman year and four-year graduation rates. Additionally, higher advisor VA increases high-ability students' likelihood of enrolling and graduating with a STEM degree. Our results indicate that allocating resources towards improving the quality of academic advising may play a key role in promoting college success.
Keywords: I23; I24; J16; 330; college completion; STEM; academic advising; value-added